1999
DOI: 10.1302/0301-620x.81b1.8971
|View full text |Cite
|
Sign up to set email alerts
|

The tourniquet in total knee arthroplasty

Abstract: We assessed the influence of the use of a tourniquet in total knee arthroplasty in a prospective, randomised study. After satisfying exclusion criteria, we divided 77 patients into two groups, one to undergo surgery with a tourniquet and one without. Both groups were well matched. The mean change in knee flexion in the group that had surgery without a tourniquet was significantly better at one week (p = 0.03) than in the other group, but movement was similar at six weeks and at four months. There was no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
96
0
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 0 publications
6
96
0
6
Order By: Relevance
“…Like Wakankar et al [17], we found that complication rates associated with TKA were the same with or without use of a tourniquet. Harvey et al [7] found the incidence of DVT was unrelated to tourniquet use, whereas others observed an increased incidence [14].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Like Wakankar et al [17], we found that complication rates associated with TKA were the same with or without use of a tourniquet. Harvey et al [7] found the incidence of DVT was unrelated to tourniquet use, whereas others observed an increased incidence [14].…”
Section: Discussionsupporting
confidence: 82%
“…We used a pressure of 350 mmHg in this study; however, pressure may vary according to surgical staff. For example, studies using twice the patient's systolic blood pressure have been reported [2,14,17]. In such cases pressure is not uniform because it is governed by the individual's systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…13 The recovery of knee flexion in the early postoperative period has been shown to be significantly better when a tourniquet has not been used. 9,14,15 Skeletal muscle may be more sensitive to an ischemic condition than peripheral nerves. 16 The use of the tourniquet is considered to be a risk for nerve injury in the affected extremity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore bosentan has shown promising results in prevention of ischemic skeletal muscle necrosis [12,15,26] and tissue protection in different organs (liver, kidney, lung, heart, brain) in case of infection and sepsis [22,31,35,8]. As a result of the low incidence, larger study groups are necessary for determining specific ET-1 release kinetics in patients with wound healing disorders and early infections to indicate a prophylactic effect of ET-1 antagonists, bosentan being the most promising candidate.…”
Section: Discussionmentioning
confidence: 99%